Health assessment of lead fusion workers in Baghdad - Samia Khalil Mahmood; Husain ode; Mohammad mossa; Khalaf Y. Shamkhy; Falah Hanash Nahar; Imad Ibrahim Ali Al-Sultan (Design for Scientific Renaissance, 2012)
Two locations of leads fusion factories in Baghdad (Altaji and Jiflic) have been selected as a high polluted area with leads; due to melting leads plates extracted from the old batteries vehicles. Samples of blood and urine have been taken from about 30 workers of each of the aforementioned locations. These samples has been divided into two different category, the first category is of age 8-18 years and the second category of age 20-60 years, taking into consideration the time they have spent working at these locations. Blood and urine samples was also collected from about 30 male pioneer donors of age range18-60 living in different parts of Baghdad and far away from the polluted factories locations that considered as control group. The results show high level of lead in the blood of the first category age 55.23 g/dl in comparison with the second category age 56.53 g/dl, whilst in urine tests the second category shows 564.83 g/L which surmount on the first category 551.8 g/L. Blood and urine samples of control group reflecting the leads pollution status to the environment of Iraq which requires taking some precaution procedures in this regard.